2003
DOI: 10.1136/gut.52.9.1304
|View full text |Cite
|
Sign up to set email alerts
|

Telomere shortening of epithelial cells characterises the adenoma-carcinoma transition of human colorectal cancer

Abstract: Background and aims: Chromosomal instability is one of the most consistent markers of sporadic colorectal cancer in humans. There is growing evidence that telomere shortening is one of the mechanisms leading to chromosomal instability and cancer initiation. Methods: To test this hypothesis, the telomere length of colorectal epithelial cells and cells from connective tissue was determined at the adenoma-carcinoma transition at the cellular level by quantitative fluorescence in situ hybridisation. Results: Our s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
41
2
2

Year Published

2004
2004
2011
2011

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(49 citation statements)
references
References 23 publications
4
41
2
2
Order By: Relevance
“…Telomere stability has been extensively correlated with the risk of cancer (Callen and Surralles 2004;Engelhardt et al 1997;Griffith et al 1999;Meeker 2006;Plentz et al 2003;Sieglova et al 2004), and few studies have investigated the relationship of Zn with telomere stability (Nemoto et al 2000;Bae et al 2007;Liu et al 2004). Accumulation of cells with short telomeres, which may lead to telomere end fusions, was found to be associated with reduced Zn status in hypertensive patients (Cipriano et al 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Telomere stability has been extensively correlated with the risk of cancer (Callen and Surralles 2004;Engelhardt et al 1997;Griffith et al 1999;Meeker 2006;Plentz et al 2003;Sieglova et al 2004), and few studies have investigated the relationship of Zn with telomere stability (Nemoto et al 2000;Bae et al 2007;Liu et al 2004). Accumulation of cells with short telomeres, which may lead to telomere end fusions, was found to be associated with reduced Zn status in hypertensive patients (Cipriano et al 2009).…”
Section: Discussionmentioning
confidence: 99%
“…However, the meaning of telomere length is a complicated subject. While it has been shown that telomere length correlates inversely, and telomerase activity directly, with malignancy in epithelial tumors, [6][7][8][9] only a couple of studies address this question in soft tissue tumors. 22,23 Bonatz et al measured telomere length in 107 uterine leiomyomas using a Southern blot method and found that telomeres were significantly shorter in tumoral tissue compared to adjacent uterine smooth muscle.…”
Section: Discussionmentioning
confidence: 99%
“…However, since there is a 50% chance that the same X-inactivation could occur incidentally between two tumors, more cases should be analyzed using this method. Telomere shortening, a possible crucial event leading to chromosomal instability and development of malignancy, has been reported in multiple types of human cancer [6][7][8][9] and can be demonstrated with telomerespecific fluorescence in situ hybridization (FISH) probes.…”
mentioning
confidence: 99%
“…In line with this hypothesis over 80% of human malignant tumors show reactivation of telomerase (Satyanarayana et al, 2004) and many genes of the senescence pathway are mutated in human cancer, for example, p53, p21 (Stewart and Weinberg, 2000). In contrast, human cancers including HCC are characterized by the presence of critical short telomeres compared to longer telomeres in noncancerous surrounding tissue (Plentz et al, 2003(Plentz et al, , 2004. Studies in mTERC À/À mice have revealed an explanation for this apparent paradox showing that telomere shortening has a dual role in cancer formation (Rudolph et al, 1999;Artandi et al, 2000).…”
Section: Introductionmentioning
confidence: 96%